Influences of outriggers lifting on aerodynamic drags and skiing time in the para-alpine sit-ski - Akashi, K.; Yamanobe, K.; Shirasaki, K.; Suzuki, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2021)
The purpose of this study was to investigate how much aerodynamic drags could reduce and how much skiing time could be shorter by lifting one side or both side outriggers forward while riding the para-alpine sit-ski. For this purpose, 4 sit-skiers were measured aerodynamic forces when taking the three positions (Normal position; putting both outriggers down a body side, Position lifting one side; lifting only one side outrigger forward, Position lifting both sides; lifting both sides outriggers forward) in a wind tunnel. Furthermore, the skiing simulation was run using the result of the wind tunnel test. The results of the wind tunnel test, drag areas were 0.360 ± 0.024 - 0.364 ± 0.030 m2 in the normal position, 0.307 ± 0.029 - 0.318 ± 0.037 m2 in the position lifting one side, and 0.229 ± 0.026 - 0.239 ± 0.029 m2 in the position lifting both sides. Thus, aerodynamic drags decreased by approximately 15% by lifting one side outrigger forward and by approximately 35% by lifting both sides outriggers forward compared with the normal position. Especially, the position lifting both sides was smaller both projected areas and drag coefficients than the normal position. Thus, it is considered that the position lifting both sides decreased aerodynamic drags than the normal position by reducing projected areas of arms and outriggers and changing wholes of skier`s system to shapes which are less sensitive to aerodynamic drags.The results of the skiing simulation, it was needed that skiing distances of more than 34 m in the position lifting one side and more than 21 m in the position lifting both sides to shorten by more than 0.01 s compared with the normal position. It is considered that there is no effect on shortening a skiing time if skiers cannot lift one or both sides outriggers forward longer than those distances because time is measured in units of 0.01 s in the para-alpine skiing. On the other hands, due to be compressed skiing time according to the sport classes, which are classified by degrees of skier's impairments, in the para-alpine skiing, the effects on shortening a skiing time by lifting outriggers forward are also compressed according to the sport classes. Therefore, it is necessary to decide whether lifting the outriggers forward or not according to the condition such as skiing distances and skier`s sport classes.